Knowledge and utilization of malaria control measures by pregnant and newly delivered mothers in Ibadan, Nigeria (2011)
Background: The World Health Organisation (WHO) guidelines for the control of malaria during pregnancy include prompt and effective case management of malaria combined with prevention of infection by insecticide-treated nets (ITNs) and intermittent preventive treatment in pregnancy (IPTp). Despite this the uptake is poor. Objective: To describe the malaria prevention measures utilized by these women in this environment. Methods: Information was obtained from consented pregnant and newly delivered women on their socio-demographic characteristics, knowledge and use of malaria chemoprophylaxis Results: One Thousand three hundred thirty (1330) pregnant and newly delivered women in 132 facilities within the Ibadan metropolis were surveyed. The mean age of the respondents was 29. 67 years (±5.21). The modes of prevention most commonly reported as being effective were the use of insecticide spray, window nets and ITN. Only 28.2% were using ITNs in the index pregnancy, and 67.2% of the women had had a drug administered for prophylactic purposes in the index pregnancy. Conclusion: This study demonstrates awareness but poor use of control measures. Additionally, there is poor use of the recommended agent for IPT. The factors militating against the use of these preventive measures need to be urgently explored and addressed.